Stroke in Adults With Congenital Heart Disease: Incidence, Cumulative Risk, and Predictors - Lanz, Jonas; Brophy, James M; Therrien, Judith; Kaouache, Mohammed; Guo, Liming; Marelli, Ariane J (Circulation (New York, N.Y.), 2015)
Stroke is an important cause of morbidity and mortality, although there is a lack of comprehensive data on its incidence, cumulative risk, and predictors in patients with adult congenital heart disease. This retrospective study of 29 638 Quebec patients with adult congenital heart disease aged 18 to 64 years between 1998 and 2010 was based on province-wide administrative data. The cumulative risk of ischemic stroke estimated up to age 64 years was 6.1% (95% confidence interval [CI], 5.0-7.0%) in women and 7.7% (95% CI, 6.4-8.8%) in men; the risk of hemorrhagic stroke was 0.8% (95% CI, 0.4-1.2%) and 1.3% (95% CI, 0.8-1.8%), respectively. Compared with rates reported for the general Quebec population, age-sex standardized incidence rates of ischemic stroke were 9 to 12 times higher below age 55 years and 2 to 4 times higher in the age group 55 to 64 years; hemorrhagic stroke rates were 5 to 6 times (age <55 years) and 2 to 3 times higher. Using a combination of stepwise model selection and Bayesian model averaging, the strongest predictors of ischemic stroke were heart failure (odds ratio for age group 18-49 years, 5.94 [95% CI, 3.49-10.14], odds ratio for age group 50-64 years, 1.68 [95% CI, 1.06-2.66]), diabetes mellitus (odds ratio, 2.33 [95% CI, 1.66-3.28]), and recent myocardial infarction (odds ratio, 8.38 [95% CI, 1.77-39.58]). Among patients with adult congenital heart disease, 1 in 11 men and 1 in 15 women experienced a stroke between ages 18 and 64 years. Stroke incidence was considerably higher than in the general population, especially at a younger age. The most important predictors of ischemic stroke were heart failure, diabetes mellitus, and recent myocardial infarction. Additional research is required to see whether advances in the management of adult congenital heart disease may reduce this substantial stroke rate.